USING JEOPARDY GAME TO IMPROVE STUDENTS’ VOCABULARY KNOWLEDGE - Alimudin Majda; Gunawan Agus (Lingua, 2018)
Learning english vocabulary using jeopardy game technique make the studentsfeel interesting and grasping new words easily. Therefore, the purpose of this researchis to find out whether or not there is significant effect of jeopardy game on grade sevenstudents’ vocabulary knowledge. The sampels were taken using cluster randomsampling technique, with the total number of sampels are 74 students which aredivided into two classes. The location is at MTs Al-Ihsan Bekasi. The research methodadopted was quasi experimental with research design was post-test only control group.To collect data, the students were given instruments in the form of objective, multiplechoice each numbering 30 for both control class and Experimental class. The findingsshowed that the jeopardy class students got mean score 80 higher than non-jeopardyclass students who got 77. It indicates that there is a significant difference in each classand can be seen from the analysis using one way ANOVA that produced (Sig.) valueof 0.002 was smaller than (<) Alpha 0.05, Ho is rejected and HA is accepted. Itshowed tha there is significant effect of jeopardy game on grade seven students’vocabulary knowledge at Mts Al-Ihsan Bekasi in the Academic Year of 2016-2017.